Respostas

2012-12-14T00:08:37-02:00

2x² , não é ? Porque se for...

 

A) (3x³ + 2x² - 4x ) + ( x² + 3x - 1) =  3x³ + 3x² - 1x -1

B) (3x³ + 2x² - 4x ) - ( x² + 3x - 1) =   3x³ + 2x²- 4x -x²-3x + 1 = 3x³ + x² - 7x +1

C) 4 .  (3x³ + 2x² - 4x ) = 12x³ + 8x² - 16x

D) 2 .   (3x³ + 2x² - 4x ) - 5. (x² + 3x - 1) = 6x³ + 4 x² - 8x - 5x² - 15x + 5 = 6x³ -x² - 23x + 5

E)   (x² + 3x - 1) .  (4x -2)  + (3x³ + 2x² - 4x) = 4x³ + 12x² -4x -2x² - 6x + 2 + 3x³ +2x² - 4x =  7x³ + 12x² -14x + 2 

F) (4x-2)² = (4x)² - 2 . (4x) . (2) + (2)² = 16x² - 16x + 4

7 4 7